EFFORTS TO ADDRESS CHILD SOLDIERS IN THE CENTRAL AFRICAN REPUBLIC - Muhammad Fajhriyadi Hastira; Relya Aula Thoyibah; Wafiq Azizah (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2026)
Children are a vulnerable group at risk of being recruited as child soldiers in the armed conflicts that have been taking place in Africa in recent years. This research aims to analyze efforts to end the recruitment and use of child soldiers in the Central African Republic (CAR). It will focus on explaining the efforts made by UNICEF using a negotiation management perspective, specifically William Ury's third-party negotiation theory. The present study employs a comprehensive literature review and meticulous document analysis of books, scientific journals, news articles, official documents from the Central African Republic government, UNICEF, and other relevant reports. The findings of this study indicate that UNICEF's strategic mediation has successfully freed and reintegrated thousands of children. However, challenges remain due to mistrust and resource constraints. This study makes a significant contribution to the field of conflict resolution research by emphasizing negotiation as a multidimensional approach worthy of consideration for addressing the issue of child soldiers in complex humanitarian crises.